Iterated boolean sums of Bernstein and related operators - Raşa, Ioan (Rev. Anal. Numér. Théor. Approx., 2006)
Let \((T(t))_{t≥0}\) be the semigroup associated with the classical Bernstein operators \((B_{n})_{n≥1}\) on \(C[0,1]\). We obtain rates of convergence for iterated boolean sums of the operators \(T\left( \frac{1}{n}\right) .\)